Guardian bones: burials in the walls of multi-family residences in Marcahuamachuco, Peru - Gayoso Rullier, Henry (2023)
This paper introduces the finding of mural burials in building A, Cerro de las Monjas sector, at Marcahuamachuco archaeological site. Building A is part of a set of multifamily residences. A description and analysis of bone remains is made. Finally, according with ethnographical data, we suggest the role of the buried individuals’ souls as guardians and protectors of the buildings and their occupants.